In Vitro Inhibitory Effects of 8-O-Demethylmaritidine and Undulatine on Acetylcholinesterase and Their Predicted Penetration across the Blood-Brain Barrier - Cahlíková, Lucie; Pérez, Daniel I; Štěpánková, Šárka; Chlebek, Jakub; Šafratová, Marcela; Hošt'álková, Anna; Opletal, Lubomír (Journal of natural products, 2015)
Alzheimer's disease is the most common cause of dementia. Currently, acetylcholinesterase (AChE) inhibition is the most widely used therapeutic treatment. A large number of naturally occurring compounds have been found to inhibit AChE. In this report the mechanism of AChE inhibition of two Amaryllidaceae alkaloids, 8-O-demethylmaritidine (1) and undulatine (2), and their possible penetration across the blood-brain barrier have been studied. Both compounds act via a mixed inhibition mechanism. Based on the parallel artificial permeation assay (PAMPA) for the prediction of blood-brain barrier (BBB) penetration, only 2 should be able to cross the BBB by passive permeation.
Keywords: hematoencefalická bariéra; cholinesterasové inhibitory; In Vitro Techniques; Acetylcholinesterase; Blood-Brain Barrier; Molecular Structure; Amaryllidaceae Alkaloids; biologický transport; techniky in vitro; Humans; alkaloidy amarylkovitých; lidé; Alzheimer Disease; Alzheimerova nemoc; acetylcholinesterasa; Cholinesterase Inhibitors; Biological Transport; molekulární struktura